The choice of exchange rate regimes in developing countries: A mulitnominal panal analysis - Jürgen von Hagen; Jizhong Zhou (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper analyses the choices of exchange rate regimes in developing countries since 1980. Static and dynamic random-effects multinominal panel models are estimated using simulation-based techniques. Explanatory variables include OCA fundamentals, stabilization considerations, currency crises factors, and political and institutional features. The results reveal strong state dependence in regime choices.
Keywords: F33; F41; C25; 330; exchange rate regimes; developing country; multinomial logit model; static and dynamic panel; simulation; Wechselkurssystem; Wechselkurspolitik; Schätzung; Entwicklungsländer